Prenylated flavonoids with potential antimicrobial activity: Synthesis, biological activity, and in silico study - Osorio, Mauricio E. (2021)
Fil: Fil: Osorio, Mauricio. Universidad Técnica Federico Santa María, Departamento de Química. Chile.